The Heuristic Evaluation of Web-Sites Concerning the Evaluators' Expertise and the Appropriate Criteria List - Athanasis KAROULIS; Andreas POMBORTSIS (Informatics in Education, 2004)
Research for the evaluation of web-sites has already begun, however it is proceeding at a very slow rate. The main reasons for this are, in our opinion, the attempt to adapt existing methodologies to the particularities of the web, the individual structure of web-sites and the issue of finding the appropriate evaluators. This study copes exactly with these points and suggests a heuristic approach for the evaluation of web-sites.